Enigmatic Rapidly Enlarging Nasal Mass That Is Not Cancer - Trilok Shrivastava; Lin Li; Sonia Tanwar; Rabab Nasim; Vincent Gullas; Jay Pescatore; Michael Nelson (Case Reports in Dermatological Medicine)
Cutaneous blastomycosis is not rare, but progressively enlarging nasal mass as the only presentation with nondiagnostic biopsy results, presence of pulmonary fibrosis, nodules and lymphadenopathy, and urinary sediments, as well as ANA and p-ANCA positivity, can make things more cryptic than expected.